Analysis of the Cooperative Learning Effectiveness on Students’ Critical Thinking Skills in Science Learning for Primary Students - Esti Mutia Hayati; Agung Purwanto; Dede Rahmat Hidayat (AL-ISHLAH: Jurnal Pendidikan, 2023)
Elementary school students' lack of critical thinking skills in scientific learning is a result of a lack of opportunities for kids to exercise their critical thinking skills in decision-making and problem-solving. Appropriate learning models and strategies in science education can help students develop their critical thinking skills. Consequently, this research aimed to examine how well cooperative learning develops students' capacity for critical thinking. This research is novel in that it will examine different journals of environmentally friendly cooperative learning models while keeping in mind the theme of the SDGs, which has not been the focus of previous studies but has shown results related to environmental insights, especially in science learning. A method of the systematic literature review was adopted for this investigation. Previous relevant scientific studies on the same topic served as the basis for this research. Data reduction, presentation, synthesis, and conclusion drawing constitute the data analysis method. Students develop their critical thinking capacity through collaborative learning strategies, including game or role-playing, Jigsaw, TGT, STAD, and learning together, and by analysing previously relevant scientific materials. Reading these relevant, previously published scientific publications can bolster students' knowledge and ability to think critically and creatively. For topics not covered here, such as the effects of cooperative learning with an ecological lens on students' critical thinking, this study can serve as a useful resource.